2008
DOI: 10.1117/12.791850
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension of line width roughness and its effects on transistor performance

Abstract: The effects of Line Width Roughness (LWR) on transistor performance are one of the hottest issues in semiconductor industry. However, in most related studies, LWR is considered as the fluctuations of gate lengths and not of resist lines. In this paper, we examine the direct effects of one of the spatial resist LWR parameters, the fractal dimension, on transistor off current deviations for various correlation lengths and gate widths. The aim is to exploit the fractality of LWR in order to link the gap between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The main findings of the paper are summarized in the final Section VI. In previous works of our group [5]- [7], we have shown that for fixed design transistor parameters, the lowering of the spatial LWR parameters of the manufactured long lines improves the reliability of the fabricated transistors. The present work completes this finding by examining the role of a basic design parameter in the LWR degradation effects on transistor operation.…”
Section: Introductionmentioning
confidence: 87%
“…The main findings of the paper are summarized in the final Section VI. In previous works of our group [5]- [7], we have shown that for fixed design transistor parameters, the lowering of the spatial LWR parameters of the manufactured long lines improves the reliability of the fabricated transistors. The present work completes this finding by examining the role of a basic design parameter in the LWR degradation effects on transistor operation.…”
Section: Introductionmentioning
confidence: 87%
“…Thus the connection of lithographic LER/LWR studies with GLR effects on transistor performance pass through the examination of spatial LER/LWR parameters ξ,α. In this context, we have evaluated the effects of lithographic ξ,α on transistor performance and presented the results in previous contributions of our group to SPIE [9][10][11]. The main finding was that correlation length affects mainly the deviations from the nominal threshold voltage of a planar MOSFET, while the off state leakage current is more sensitive to changes of the roughness exponent.…”
Section: Fig2mentioning
confidence: 95%
“…As referred to in Section 16.2.2, resist LWR (rms value) has been agreed to be measured in lines longer than 2 μ m (Constantoudis et al ., 2004;;Leunissen et al ., 2004;Yamaguchi et al ., 2005;Patsis et al ., 2006;Constantoudis and Gogolides, 2008;Constantoudis et al ., 2012.). On the other hand, GLR is defi ned in lengths equal to the gate widths, which are usually some multiples of CD (~20-40 nm) i.e much shorter than 2 μ m. Given the dependence of rms value on edge length (see Section 16.2.2), this length difference translates to differences in the rms values of LWR and GLR.…”
Section: Impact On Device Performancementioning
confidence: 98%
“…One can notice the sharing of resist LWR of long lines into GLR and CD variation as well as the critical role of the spatial LWR parameters ( ξ , α ) in the control of this partition(Constantoudis and Gogolides, 2008). Dependence of the average threshold voltage shift δ V th (a), the standard deviation σ ( δ V th ) (b), the average I off / I off,ideal (c) and the standard deviation σ ( I off / I off,ideal ) on the spatial LWR parameters α , ξ .…”
mentioning
confidence: 98%